STUDENTS’ PERCEPTIONS OF ICT UTILIZATION FOR LEARNING GRAMMAR IN ONLINE CLASS - Dyah Supraba Lastari; Arjulayana Arjulayana (UICELL, 2022)
During the transition period following the Covid-19 pandemic, many education institutions around the world have implemented the integration of ICT (information and communication technology), including for English grammar online class. This research was conducted to find out students’ perceptions of the utilization of ICT for learning grammar in online settings. The subjects of this research were second semester students at Muhammadiyah University of Tangerang. The participants experienced online grammar learning by using LMS (Learning Management System); video conferencing platform; video sharing website; social media and game-based application. Researcher used questionnaires and interviews to collect data on how they perceive technology integration in grammar teaching-learning process. The findings showed that students responded positively towards the utilization of technology to facilitate English grammar teaching-learning process in online settings. Keywords: ICT, CALL, English grammar